3D fabrication of artificial cell microenvironments for mechanobiology - Sonn, Annabelle; Tomba, Caterina; Selhuber-Unkel, Christine; Schamberger, Barbara (Current opinion in biomedical engineering, 2025)
Artificial scaffolds are indispensable tools in unraveling the complexity of mechanobiology under controlled conditions. Recent breakthroughs in microfabrication techniques for biological applications have revolutionized the field, enabling well-defined features that span from the subcellular to the multicellular scale. These methods particularly allow for unprecedented control of cell stimulation. This review will showcase research that combines such scaffolds with various stimulation techniques: mechanical stimulation, actuation by magnetic or electric fields, chemical stimulation, or manipulation by light. Additionally, it will introduce passive scaffolds that are actuated by the cells themselves. These systems help to understand forces applied by the cells to their environment and pave the way toward dynamic biohybrid, cell-based systems.